A rapid solid-phase extraction combined with liquid chromatography-tandem mass spectrometry for simultaneous screening of multiple allergens in chocolates. (February 2018) - Gu, Shuqing; Chen, Niannian; Zhou, Yao; Zhao, Chaomin; Zhan, Lina; Qu, Li; Cao, Chen; Han, Li; Deng, Xiaojun; Ding, Tao; Song, Chang; Ding, Yaping
Abstract: Allergen derived from food is a world-wide problem to specific consumers. The regulation for accurate control of risk demands a fast and sensitive method for comprehensive screening and confirmation for potential allergens in foods. In this work, an optimized and sensitive LC-MS/MS method for multiplex detection of eight allergenic ingredients in chocolate matrix is proposed. Improved throughput and enhanced sensitivity were obtained by introduction of a rapid solid-phase extraction step using MonoSpin PBA spin column. The most intense and reliable peptide markers were first identified by untargeted survey experiment using quadrupole-orbitrap high resolution mass spectrometer, and subsequently employed to design a multi-target MRM method, based on the most intense transitions recorded for each selected precursor peptide. The MRM quantitative analysis was performed on triple quadrupole mass spectrometer with optimized sensitivity and reproducibility. Protein sequence coverage of 70.8–93.3% were obtained for confirmation of each allergenic ingredient and two or three most sensitive peptide markers were selected in order to retrieve quantitative information. Limits of quantification shown as 0.2–0.4 μg/g for milk, 1.0–4 μg/g for soy, 2.5–4 μg/g for peanut, 1–3 μg/g for tree nuts respectively as well as recoveries ranged from 60.1(±2.7)% to 92.4(±5.6)% for chocolate samples proved the excellent capabilities of the exploited sample treatment method combined with the LC-MS/MS analysis. Finally, this method was successfully applied to the investigation of multiple allergens in commercially available chocolates of different brands aiming to ascertain possible discrepancies between allergen content and food allergen labelling. Highlights: Use of a rapid solid-phase extraction method (3 min) for chocolate matrix. Detection of 8 allergenic ingredients by HPLC-MS/MS with good performances. Reveal the presence of undeclared allergens in commercial chocolates.